Pengaruh Kualitas Pelayanan SPBU Pasti Pas Terhadap Kepuasan Konsumen di Kota Malang (Studi Pada SPBU Pasti Pas Jalan Panglima Sudirman Kota Malang) - Pratiwi, Esti Wahyu; Rohman, Fatchur (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2012)
Quality is one factor that can affect customer satisfaction. Studies on the quality of service that consists of five variables: physical evidence, empathy, reliability, assurance and responsiveness to know how big influence on customer satisfaction. Product quality services have an important role to establish customer satisfaction. The more quality products and services delivered, the satisfaction felt by customers or consumers higher. Creation of customer satisfaction can provide benefits, including the relationship between companies and customers into harmony, providing a good basis for consumers to make repeat purchases and create customer loyalty, and gave good recommendations through word of mouth that benefit company. Customer satisfaction is the degree to which the needs, wants and expectations of customers are met that will result in repeat purchases. Therefore, the quality of service becomes very important for the company to stay ahead and maintain customer satisfaction Keywords: Service Quality, Customer Satisfaction